KEPEMIMPINAN KRISTEN INKLUSI: SEBUAH TAWARAN MODEL KEPEMIMPINAN GEREJA YANG RELEVAN DI ERA DIGITAL - Hadi, Samsu; Nugroho, Andreas Eko; Antonius, Yosef (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2025)
Church leaders who adhere to the principle of absolute power often cause dissatisfaction among church members. This dissatisfaction can escalate into conflict when the leader lacks the knowledge and ability to manage a diverse congregation. In the digital era, conflicts can intensify because congregants can freely express their dissatisfaction on social media. Thus, this research aims to examine and analyze inclusive leadership as a relevant leadership approach in the digital era. This qualitative research uses descriptive and library research methods which will discuss the nature and theological basis of Christian leadership, the characteristics of inclusive leadership and the actualization and implications of inclusive leadership.. The results show that inclusive Christian Leadership, with its five main characteristics, can solve church leadership issues in the digital era. This leadership model strengthens church ministry amid the complexity of social identity, digital transformation, and cultural disruption.